Design and analysis of low profile and low SAR full-textile UWB wearable antenna with metamaterial for WBAN applications - Husnu Yalduz; Timucin EmreTabaru; Veli Tayfun Kilic; Mustafa Turkmen (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2020)
In this paper, a low-profile wearable antenna with metamaterial (MM) for wireless body area network (WBAN) applications is presented. The designed antenna with MM operates in the ultra-wideband (UWB) between 4.55 and 13 GHz and it has a thickness of 4.68 mm. To the best of our knowledge, it is the lowest thickness reported in the literature for UWB antennas with MM. The proposed is designed and manufactured using fully flexible textiles. The designed antenna was simulated in free space and on the human body model. Simulation results show that gain, directionality, and front-to-back ratio of the antenna increase considerably with the placement of the MM. Also, in simulations, it is found that the specific absorption rate (SAR) values for the designed antenna reduce by 98.3% when MM is used. These SAR values calculated for the designed antenna with MM are well below the limits defined in European standards. The designed antenna and metamaterials were manufactured, too, and scattering parameters were measured. Measurement results are in good agreement with the results found in the simulations. It shows that the proposed antenna is very suitable for use in WBAN applications due to its low thickness, having low SAR, and UWB operation.
Keywords: Textile antenn; Metamaterial; Ultra-wideband antenna; Wireless body area network